Analisis Ziswaf Pada LAZ Sidogiri : Indonesia - Salsabila Firdaus; Meila Ilannaja; Liatul Aini (Tasharruf : Journal of Islamic Economics and Business, 2024)
Abstract This research analyzes the role of the Sidogiri Amil Zakat Institution (LAZ) in managing zakat, infaq, alms and waqf (ZISWAF) funds, as well as other humanitarian funds. As a non-profit entity, LAZ Sidogiri aims to improve the welfare of the poor and mustahik through comprehensive programs. LAZ Sidogiri's vision and mission include increasing awareness of zakat, empowering community potential, and improving the quality of life of the people through education, health, economics, social and da'wah. Flagship programs such as Kun Fayakun, Latansana, Burdah, and Hidayati are designed to provide various assistance according to community needs, ranging from basic needs assistance to business skills development and special attention to orphans. The implementation of these programs is based on the principles of Islamic sharia and Rasulullah's management, and is supported by a strong organizational culture. This research shows that through effective and strategic management, LAZ Sidogiri has succeeded in contributing significantly to improving the welfare of underprivileged communities.